Pessoas com deficiência física na microrregião do Vão do Paranã: narrativas e cartografias de vida - Passos, Jamylle Lorrane Silva (2019)
The dissertation is linked to the master's research to analyze the cities of Vão do Paranã’s microregion with a perspective aiming disabled people, verifying the historical-geographical formation process of this region since its occupation, to understand the spaces of displacement and experiences of these individuals. In the first moment, the socioeconomic disparities of this region comparing to the rest of the state of Goiás are contextualized by confronting census data based on an analysis scheduled by “Municipal Human Development Index” and Taxes on Merchandise and Services, therefore seeking to understand the most evident socioeconomic deficits on the chosen location. In the second stage, the number of disabled people was recorded in the micro-region of Vão do Paranã according to data from the Brazilian Institute of Geography and Statistics, so the quantity of these people was obtained. In the third and final stage the exhibition of the results is presented, using the methodology of the narratives to report life stories that were told through interviews. In view of these experiences, existential cartographies were created for the main subject of this dissertation, presenting the anguishes, fears, achievements, joys and wishes of disabled people living in the microregion of Vão do Paranã.